1984
DOI: 10.1172/jci111404
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and inotropic potential of forskolin in the human heart.

Abstract: As bstract. We evaluated the effects of the diterpene compound forskolin in human myocardial adenylate cyclase preparations, isolated trabeculae and papillary muscles derived from failing human hearts, and acutely instrumented dogs. Forskolin was a potent, powerful activator of human myocardial adenylate cyclase and produced maximal effects that were 4.82 (normally functioning left ventricle) and 6.13 (failing left ventricle) fold greater than isoproterenol. In contrast to isoproterenol, forskolin retained ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
3

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(47 citation statements)
references
References 29 publications
2
42
3
Order By: Relevance
“…In all studies, cardiac output and heart rate increased during forskolin administration, but in two of the animals there was no change in either variable until the last two drug dosages. This blunted increase in cardiac output has also been seen in open-chest dogs, but this was believed to be secondary to a decrease in left atrial mean pressure which occurred to a greater extent with forskolin than isoproterenol (8). In contrast, in the present study we demonstrated no significant difference in mean pulmonary capillary wedge pressure which would suggest there was no significant change in left atrial mean pressures.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In all studies, cardiac output and heart rate increased during forskolin administration, but in two of the animals there was no change in either variable until the last two drug dosages. This blunted increase in cardiac output has also been seen in open-chest dogs, but this was believed to be secondary to a decrease in left atrial mean pressure which occurred to a greater extent with forskolin than isoproterenol (8). In contrast, in the present study we demonstrated no significant difference in mean pulmonary capillary wedge pressure which would suggest there was no significant change in left atrial mean pressures.…”
Section: Discussionsupporting
confidence: 49%
“…In contrast, in the present study we demonstrated no significant difference in mean pulmonary capillary wedge pressure which would suggest there was no significant change in left atrial mean pressures. Previous work had also demonstrated a significant decrease in mean arterial pressure with administration of isoproterenol and forskolin (8). In our study neither of these variables changed significantly, although the marked increase in cardiac output associated with no change in arterial pressure would indicate that forskolin has pulmonary and systemic vasodilating properties, although again to a lesser extent that isoproterenol.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…A recent study has shown that type V mRNA is present also in the kidney in the rat, suggesting that distribution oftype V mRNA expression occurs in a species-specific manner (28). 4 --Reported adenylylcyclase catalytic activities in heart failure have been variable, with some studies demonstrating a decrease in basal activity (5,29) and others demonstrating a normal basal and stimulated adenylylcyclase activity (30). Direct evaluation of catalytic unit activity has been difficult; crude membranes can be variably contaminated with GTP and this could differ among the particular membrane preparations used.…”
Section: Discussionmentioning
confidence: 99%